2010
DOI: 10.1016/j.jedc.2010.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Short-run fiscal policy: Welfare, redistribution and aggregate effects in the short and long-run

Abstract: This paper quantifies the effects of two short-run fiscal policies, a temporary tax cut and a temporary rebate transfer, that are intended to stimulate economic activity. A reduction in income taxation provides immediate incentives to work and save more, raising aggregate output and consumption. A temporary rebate is mostly saved and increases consumption marginally. Both policies improve the overall welfare of households, and the rebate policy especially benefits low-income households. In the long run, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…The government is assumed to have three …scal measures to …nance each of the two consolidation plans: (i) the income tax rates, (ii) the consumption tax rate and (iii) transfer payments. 23 The adjustments in income or consumption taxes or transfer payments are made to balance the government budget constraint in (7) from year 2015 onwards. While it is straightforward to implement the consumption tax adjustments via temporary increases in the e¤ective consumption tax rate, c t , additional assumptions need to be made for the other two measures.…”
Section: Methodsmentioning
confidence: 99%
“…The government is assumed to have three …scal measures to …nance each of the two consolidation plans: (i) the income tax rates, (ii) the consumption tax rate and (iii) transfer payments. 23 The adjustments in income or consumption taxes or transfer payments are made to balance the government budget constraint in (7) from year 2015 onwards. While it is straightforward to implement the consumption tax adjustments via temporary increases in the e¤ective consumption tax rate, c t , additional assumptions need to be made for the other two measures.…”
Section: Methodsmentioning
confidence: 99%
“…It was found that tax incentive would enhance economic growth and development in Nigeria, if such incentives are well focused and extended to all deserving companies in the country. Kitao (2010) found that fiscal policy, tax-reduction and discount transfer enhance the well-being of individuals and the discount policy achieve advantages for low-income individuals.…”
Section: Empirical Reviewmentioning
confidence: 98%
“…Economic slowdown modelled through reduced g directly affects net government debt that increases by additional 19 percentage points of GDP relative to the benchmark model simulation of the baseline transition. 24 The reduced tax revenues and increased expenditures on pensions and interest payments require further cuts in government consumption that is assumed to clear the government budget constraint during the baseline transition.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Similarly to other developed countries, population ageing in Australia is expected to accelerate in the next several decades, reducing population growth and generating a significantly higher proportion of the elderly in the total population. In this subsection, we examine the long run macroeconomic effects of keeping the existing budget deficit to GDP ratio unchanged (as under 24 In the long run steady state, the net government debt to GDP ratio equals to Deficit GDP/ (n + g + ng) , which with g = 1%, n = 1.6% and Deficit GDP = 3.07% implies net government debt of 117.35% of GDP, compared to 98.27% of GDP reported in Section 4.…”
Section: Population Ageingmentioning
confidence: 99%